Método fônico: do sucesso da aprendizagem em alfabetização ou do retorno à inexistência sócio-histórica do sujeito da linguagem - Gallert, Claudia (2013)
The phonic method has been presented by its proponents as a solution to eliminate the Brazilian failure of children in reading and writing, correcting problems in literacy. Understand that the literacy is not restricted to the application of a savior method teaching, learning as collateral or as an initial phase of schooling. First, it is a job with the language, and therefore, every form of forward pedagogical work for literacy is associated with a conception of language. This research has been devoted to the analysis of the activities of the Student BookLiteracy phonic: building competence in reading and writing, by Seabra Capovilla (2010), to find elements that allow to identify which language conception that supports the orientation of phonic method to literacy. The Bakhtinian perspective grounded discussion of this research on the formation of literacy as a sign and as a sphere of human activity, therefore a field ideological disputes. From there, we discussed how the relationship between teaching practice, methodological and language conception influence social relationships within the school, in the processes of teaching and learning, expressing a certain understanding of subject and society.